Field report, summer 1999, Bruce Ehresman - Ehresman, Bruceet al (1999)
An annotated list of birds sighted by Bruce Ehresman. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1999. Epson - sheet feed